Study of lignite humic acids hybrid modification technology of biodegradable films based on polyvinyl alcohol - Lebedev, Vladimir Vladimirovich; Miroshnichenko, Denis Viktorovich; Tykhomyrova, Tetyana Sergiivna (РС Теshnology сentеr, 2023)
Object of article study is lignite humic acids hybrid modification technology of biodegradable films based on polyvinyl alcohol. The possibility of increasing the strength and operational properties of biodegradable polymeric materials based on polyvinyl alcohol by using its modification with the different types of humic acids from lignite is considered. Lignite humic acids hybrid modification films with antibacterial properties were obtained. The twostage technology of lignite humic acids hybrid modification of biodegradable films based on polyvinyl alcohol was formalized. At the first stage of lignite humic acids hybrid modification technologies for hybrid-modified biodegradable materials production, lignite humic acids are received. At the second stage, hybrid modification of lignite humic acids (that are part of biodegradable polyvinyl alcohol films), which are received by watering from a solution, takes place. It has been conducted a study on determining the effect of lignite humic acids hybrid modification on the most important operational properties of biodegradable film based on polyvinyl alcohol, i. e., tensile strength, relative elongation at break and time of mold appearance. Changes in tensile strength, relative elongation at break and time of mold appearance for the lignite humic acids hybrid modified biodegradable polymeric materials based on polyvinyl alcohol were revealed depending on the content of the different types of lignite humic acids. It was also shown that the lignite humic acids hybrid modification of polyvinyl alcohol with the different types of humic acids allows preserving the biodegradability of the films along with imparting the antibacterial properties. The developed lignite humic acids hybrid modified biodegradable polyvinyl alcohol films with antibacterial properties, in terms of their operational characteristics, are superior to the known similar bio degradable films based on natural biopolymers.
Keywords: brown coal; humic acids; hybrid modification; polyvinyl alcohol; antibacterial properties; biodegradable films; буре вугілля; гумінові кислоти; гібридна модифікація; полівініловий спирт; антибактеріальні властивості; біорозкладні плівки